2020
DOI: 10.1021/acsaelm.0c00166
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Electron-Transport Layer Incorporated Highly Efficient OLED

Abstract: The realization of highly efficient devices depends on efficient charge carrier injection, employment of materials, and proper fabrication methodologies. However, it is difficult to manufacture highly efficient large-area devices due to the varied thickness of organic layers and low mobility of charge carriers. Solution and thermal evaporation processes have been reported for the fabrication of highly efficient and long-lifetime organic light-emitting diodes (OLEDs). This work reveals appropriate performance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…11–14 However, the devices are fabricated using a thermal evaporation process which makes the process overall quite expensive with numerous disadvantages such as high-power consumption, restrictions in scalability, decreased throughput, high rate of material consumption, complex color patterning process and non-uniform film deposition for large area fabrication while maintaining an enhanced resolution in pixels. 15–17 This also delays the further commercialization and adoption of the OLED technology due to the high costs involved. The adoption of solution-processable fabrication processes can mitigate this problem by providing an inexpensive pathway for the fabrication of large-area efficient devices with a much higher utilization rate of materials.…”
Section: Introductionmentioning
confidence: 99%
“…11–14 However, the devices are fabricated using a thermal evaporation process which makes the process overall quite expensive with numerous disadvantages such as high-power consumption, restrictions in scalability, decreased throughput, high rate of material consumption, complex color patterning process and non-uniform film deposition for large area fabrication while maintaining an enhanced resolution in pixels. 15–17 This also delays the further commercialization and adoption of the OLED technology due to the high costs involved. The adoption of solution-processable fabrication processes can mitigate this problem by providing an inexpensive pathway for the fabrication of large-area efficient devices with a much higher utilization rate of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications have been applied to both anode/organic and cathode/organic interfaces, which intends to 1) reduce the injection barrier through modification of electrode work function or introduction of an interfacial charge separation layer/dipole layer, 2) narrow the injection barrier through the interfacial doping to enable tunneling, and 3) reinforce the interfacial electric fields for carrier injection by modification of the electrode surface. Utilization of NPs has been demonstrated as an effective and versatile strategy for carrier injection enhancements at electrode/organic interfaces due to the variable and unique electronic properties of NPs, and a variety of NPs [ 41–56 ] have been incorporated into various layers of OLEDs for carrier injection abilities improvement.…”
Section: Various Roles Of Nps In Oledsmentioning
confidence: 99%
“…In addition, metal oxide NPs such as Fe 3 O 4 , [ 45,46 ] NiO x , [ 47 ] SnO 2 , [ 48,49 ] MoO 3 , [ 54 ] ZnO, [ 55 ] TiO 2 , [ 56 ] etc., have also been introduced as efficient buffer layer or carrier injection layer in OLEDs, which also resulted in improved carrier injection abilities and thus device efficiencies. Sun's group demonstrated that Fe 3 O 4 modified anode in both bottom and top emitting OLEDs enables improved hole injection from anode and thus enhanced device efficiency, which stemmed from the formation of dipole layer and thus reduced hole injection barrier at the anode/organic interfaces (Figure 2f).…”
Section: Various Roles Of Nps In Oledsmentioning
confidence: 99%
“…However, even after applying compensation outside and inside the panel to improve grayscale expression, the method used to drive the AMOLED display cannot ensure good image quality at extremely low luminance, because the current controlled by the driving thin-film transistors (TFTs) is affected by the square terms of the potential difference between the gate and the source. Furthermore, it has been more difficult to precisely control the gray scale on the AMOLED display because of the sharply decreased the current in unit pixel as increasing resolution over the 400-600 ppi and drastically increased OLED efficiency [14,15] and the improvement of the panel power consumption.…”
Section: Contact Hyun Jae Kimmentioning
confidence: 99%